Nachhaltige Regionalentwicklung und kooperativer Naturschutz in Süd-Korea. Governance-Prozesse im Jeju Island Biosphere Reserve im Vergleich mit Biosphärenreservaten in Deutschland und Großbritannien - Kim Pollermann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Biosphärenreservate bieten einen Rahmen für Prozesse zur nachhaltigen Regionalentwicklung. Durch das Beispiel des Biosphärenreservats Jeju Island sowie einen internationalen Vergleich werden Hinweise für eine erfolgversprechende Ausgestaltung aufgezeigt. Nach einem Überblick zum Vorgehen der Untersuchungen werden zunächst die spezifischen Rahmenbedingungen in Süd-Korea sowie das Biosphärenreservat Jeju Island vorgestellt. Daraufhin werden empirische Ergebnisse im Vergleich mit deutschen und britischen Biosphärenreservaten dargelegt und schließlich Empfehlungen abgeleitet. – – Biosphere reserves as a category for integrative protected areas can serve as a suitable framework for promoting sustainable regional development and supporting nature conservation. As the practical implementation of the theoretical approach is very different across the world, an international comparison is useful to create more knowledge about adequate solutions for typical problems like a lack of acceptance or organizing participation. The introduction to boundary conditions in South-Korea and their impact on environmental awareness is followed by the description of the biosphere reserve Jeju Island including an analysis of the project implementation eight years after the decision on a management plan. Then an international comparison is presented using empirical results from Jeju Island as well as from case studies in the UK and Germany. The development in Jeju Island shows common features with the European case studies. At the end of the report similarities and differences are discussed. Conclusions are given concerning the creation of a positive image of the biosphere reserves and how to set priorities in capacity building. In this context education for sustainable development and the organisation of participation should play a crucial role.
Keywords: Q3; Q5; 330; Biosphärenreservat; Korea; Regionalentwicklung; Governance; Naturschutz; Kooperation; Südkorea; Ökotourismus; Governance-Ansatz; Regionalpolitik